Indirect carotid-cavernous fistula – diagnostic problems - Duchnik, Irmina; Babik, Anna; Poręba, Natalia; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2017)
Indirect carotid cavernous fistula is a rare vascular disorder characterized by the communication of venous blood located in the cavernous cavity, with arterial blood coming from the meningeal branch of internal carotid artery and/or external carotid artery. The slow blood flow in and around the fistula causes mild clinical symptoms; as a result, a patient may be misdiagnosed or a diagnosis may be delayed. Carotid cavernous fistula should be considered in all cases with coexistent exophthalmos, chemosis, dilated episcleral and conjunctival veins, and increased intraocular pressure. Treatment is associated with good outcomes and prognosis, as it limits ocular damage.